Organisationnel Change in the . Algerian institution A Field study at Condor Campany.Bordj Bou Arreridj.Condor - zouaoui, mokram (The journal of Teacher Researcher of Legal and political Studies, 2025)
This study examines This issue of organisationnel change within the Algerian institution. With a specific focus on Condor Company. A leading Enterprise specializing in the production of electronic and elecctricle devices. The Company has undergone a series of organisational transformations in response to internal and external environmental variables.The study highlights three principal indicators of change Organizational structure. The incentive system.and production management.Based on the field investigation conducted to explor the nature and scop of organizational change at Condor .and following a thorough analysis and interpretation of the collected data. The findings reveal that the change process has yielded significant outcame.these include a granting the production unit greater autonmy in determining its objectives.Thecompany has adopted a participatory organiazional structure that oversees performance monitoring and production managem Moreover.Condor has impemented a strategic incentive system targeting executives.supervisors.and workers alike. Withe the aim of enhancing productivity and improving performance. The company has also reinforced employee belonging and motivation through an effective training program conducted both inside and outsid the the instution.this approche has contributed to greater flexibility in performance.improved task exectution.enhanced time managment. And alignment withe contemporary work methods and technological advenements.